Patent foramen ovale closure in recreational divers: effect on decompression illness and ischaemic brain lesions during long-term follow-up. Issue 23 (13th September 2011) - Billinger, Michael; Zbinden, Rainer; Mordasini, Raffaela; Windecker, Stephan; Schwerzmann, Markus; Meier, Bernhard; Seiler, Christian
Abstract : Objective: To test the effect of patent foramen ovale (PFO) closure on neurological events in divers. Design: Prospective, non-randomised, longitudinal three-arm study. Setting: Tertiary referral centre. Population: 104 scuba divers with a history of major decompression illness (DCI). Intervention: Transcutaneous PFO closure. Main outcome measures: Baseline and three follow-up examinations with a questionnaire about health status and diving habits/accidents, transoesophageal echocardiography at baseline for PFO grading, cerebral MRI at all examinations. Results: 39 divers had no PFO, 26 had a PFO and chose to undergo percutaneous closure and 39 had a PFO, but decided not to undergo closure. The total number of dives, including those performed before baseline and those during long-term follow-up, was 81 654; 18 394 dives during the follow-up period of 5.3±0.3 years, during which there were a total of five major neurological DCI events–namely 0 in the no PFO group, 0.5±2.5/10 4 dives in the PFO closure group and 35.8±102.5/10 4 dives in the PFO no closure group (four events; p=0.045 between the PFO groups). In the groups, no PFO, PFO closure and PFO no closure, there were 1.1±2.6, 0.8±1.4, 3.3±6.9 ischaemic brain lesions, respectively, at follow-up (p=0.039 between the PFO groups)—that is, 16±42/10 4 dives in the no PFO group, 6±13/10 4 dives in the PFO closure group and 104±246/10 4 dives in the PFO no closure group (overall p=0.042; p=0.024 between the PFO groups). Conclusion: PFO closure in continuing divers appears to prevent symptomatic (major DCI) and asymptomatic (ischaemic brain lesions) neurological events during long-term follow-up.